Surface roughness characteristics effects on fluid load capability of tilt pad thrust bearings with water lubrication - Yuechang Wang; Ying Liu; Zhanchao Wang; Yuming Wang (Friction)
Abstract The effects of surface roughness characteristics on the fluid load capacity of tilt pad thrust bearings with water lubrication were studied by the average flow model. The flow factors utilized in the average flow model were simulated with various surface roughness parameters including skewness, kurtosis and the roughness directional pattern. The results indicated that the fluid load capacity was not only affected by the RMS roughness but also by the surface roughness characteristics. The fluid load capacity was dramatically affected by the roughness directional pattern. The skewness had a lower effect than the roughness directional pattern. The kurtosis had no notable effect on the fluid load capacity. It was possible for the fluid load capacity of the tilt pad thrust bearings to be improved by the skewness and roughness direction pattern control.